Technical Condition Monitoring for Telecommunication and Radioelectronic Systems with Redundancy - Zaliskyi, Maksym; Solomentsev, Oleksandr; Zuiev, Oleksiy; Pavlenko, Maksim; Zakharchenko, Iryna; Petrova, Yuliia (Electrical, Control and Communication Engineering, 2022)
The telecommunication and radioelectronic systems with redundancy are widely used in different branches of human activity. To provide the necessary reliability level of equipment, the operation system is utilized. That system contains intended use, maintenance, repair, technical condition monitoring, and others. The damages, faults and failures are usually observed during the lifecycle of telecommunication and radioelectronic systems. They can lead to deterioration of equipment technical condition. The deterioration of technical condition can be detected during observation of diagnostic variable and reliability parameter. This article concentrates on the synthesis and analysis of statistical data processing procedure for deterioration detection while operating telecommunication and radioelectronic systems with redundancy. For the purpose of reliability estimation based on different redundancy methods, statistical data processing procedure synthesis was carried out using multiple hypothesis testing and detection criterion. The analysis problem was solved using Monte- Carlo simulation method, which allowed constructing operating characteristics. The obtained results can be used in the process of design and improvement of operation systems for telecommunication and radioelectronic equipment.